Total carbohydrates quantified in sediment cores from coastal vegetated ecosystems - Inga Hellige; Aman Akeerath Mundanatt; Theresa-Marie Fett; Mirco Wölfelschneider; Jennifer Prugger; Jana K Geuer; Svenja Reents (PANGAEA, 2025)
50-cm deep sediment cores were taken in saltmarsh, seagrass, mangroves and unvegetated areas around the German Bight, Malaysia and Columbia in 2022 and 2023. Up to 3 points per ecosystem were sampled along a transect, in total 93 cores were analysed. Carbohydrates were sequentially extracted using MilliQ-water and 0.3 M EDTA for later analyses. The total carbohydrate content was assessed using the phenol-sulfuric acid assay (Dubois et al., 1956). Briefly, 100 μL of resuspended samples or extracts were mixed with 100 μL of 5% phenol solution, followed by the addition of 500 μL of concentrated sulfuric acid. The reaction mixture was incubated at room temperature for 10 minutes, then further incubated at 30°C for 20 minutes. Absorbance at 490 nm was measured using a Spectramax Id3 plate reader (Molecular Devices) and quantified against a glucose standard curve.